ANALISIS LOYALITAS KARYAWAN PT ASURANSI BUMI PUTRA CABANG PEKANBARU - Iskandar, Iskandar (Eko dan Bisnis: Riau Economic and Business Review, 2018)
This research was conducted at PT. Bumi Putra Insurance Branch Pekanbaru, using a sample of 89 people, using the Census method. Methods of data analysis using simple linear regression. Based on the test results on the variables of work discipline can be concluded that have a positive and significant effect on employee loyalty PT. Bumi Putra Insurance Branch Pekanbaru. Value R. Square explains that work discipline variables contribute to the influence of employee loyalty PT. Bumi Putra Insurance Branch Pekanbaru. Recommendations that can be proposed is that employees increase awareness in the work where the responses of respondents are in the category quite agree. This means that employees are less consistent in keeping up work such as the lack of caution in employee work is always careless in carrying out the job so as to cause harm to the company